Cardiosphere Conditioned Media Influence the Plasticity of Human Mediastinal Adipose Tissue-Derived Mesenchymal Stem Cells. Issue 11 (November 2015) - Siciliano, Camilla; Chimenti, Isotta; Ibrahim, Mohsen; Napoletano, Chiara; Mangino, Giorgio; Scaletta, Gaia; Zoccai, Giuseppe Biondi; Rendina, Erino Angelo; Calogero, Antonella; Frati, Giacomo; De Falco, Elena
Nowadays, cardiac regenerative medicine is facing many limitations because of the complexity to find the most suitable stem cell source and to understand the regenerative mechanisms involved. Mesenchymal stem cells (MSCs) have shown great regenerative potential due to their intrinsic properties and ability to restore cardiac functionality, directly by transdifferentiation and indirectly by paracrine effects. Yet, how MSCs could respond to definite cardiac-committing microenvironments, such as that created by resident cardiac progenitor cells in the form of cardiospheres (CSs), has never been addressed. Recently, a putative MSC pool has been described in the mediastinal fat (hmADMSCs), but both its biology and function remain hitherto unexplored. Accordingly, we investigated the potential of hmADMSCs to be committed toward a cardiovascular lineage after preconditioning with CS-conditioned media (CCM). Results indicated that CCM affects cell proliferation. Gene expression levels of multiple cardiovascular and stemness markers (MHC, KDR, Nkx2.5, Thy-1, c-kit, SMA) are significantly modulated, and the percentage of hmADMSCs preconditioned with CCM and positive for Nkx2.5, MHC, and KDR is significantly higher relative to FBS and explant-derived cell conditioned media (EDCM, the unselected stage before CS formation). Growth factor-specific and survival signaling pathways (i.e., Erk1/2, Akt, p38, mTOR, p53) present in CCM are all equally regulated. Nonetheless, earlier BAD phosphorylation (Ser112) occurs associated with the CS microenvironment (and to a lesser extent to EDCM), whereas faster phosphorylation of PRAS40 in FBS, and of Akt (Ser473) in EDCM and 5-azacytidine occurs compared to CCM. For the first time, we demonstrated that the MSC pool held in the mediastinal fat is adequately plastic to partially differentiate in vitro toward a cardiac-like lineage. Besides, we have provided novel evidence of the potent inductive niche-like microenvironment that the CS structure can reproduce in vitro. hmADMSCs can represent an interesting tool in order to exploit their possible role in cardiovascular diseases and treatment.